2005
DOI: 10.1021/jp0517495
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of the Interlayer Structure and the Mobility of Alkyl Chains in HDTMA+/Montmorillonite Hybrids

Abstract: Molecular simulation techniques are used to find the basal spacing of organoclay on the basis of the energy minimum, using the canonical NVT ensemble. Then, the interlayer structure and mobility of alkyl chains are explored based on the interlayer atomic density profiles. Besides the basic lateral-monolayer arrangement, lateral-bilayer accompanied by partial a pseudo-trilayer and a transition structure between the two basic lateral models are observed. The later provides an excellent explanation about the refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 42 publications
7
64
0
Order By: Relevance
“…In the case of NM-C18-2.0CEC, half of the surfactant was cations while the other half was in the form of ionic pairs. It has been shown that the ammonium head groups of surfactant cations were close to clay mineral surface due to the coulomb interaction in previous simulations [15][16][17]. The same phenomenon was found in the present simulation.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the case of NM-C18-2.0CEC, half of the surfactant was cations while the other half was in the form of ionic pairs. It has been shown that the ammonium head groups of surfactant cations were close to clay mineral surface due to the coulomb interaction in previous simulations [15][16][17]. The same phenomenon was found in the present simulation.…”
Section: Resultssupporting
confidence: 89%
“…In the case of NM-C18-S-4.0, the montmorillonite interlayer spaces are dramatically expanded from 1.5 nm (original Ca-montmorillonite) to 4.10 nm (NM-C18-S-4.0) and a paraffin bilayer arrangement of the intercalated surfactants was adopted, providing big space for adopting surfactant molecules (ionic pairs). However, in the case of NM-C8-S-4.0, the basal spacing is similar to that of the used Ca-montmorillonite, indicating a lateral monolayer arrangement of the intercalated surfactant [8,11,16]. In this case, the space for adopting surfactant molecules (ionic pairs) is limited.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In the following drying process, the relative intensity of the first reflection is shown to continually decrease in the first 6 h. Finally only one reflection appears after 6 h drying, and this reflection also shifts to smaller basal spacing value as the drying process continues. After 12 h drying, the basal spacing value of OMt0.8 appears at 1.68 nm, which means CTMA can also adopt a transition structure between lateral-monolayer and lateral-bilayer [39]. The interesting result shown in Fig.…”
Section: Basal Spacing Evolution Of Omtmentioning
confidence: 86%
“…After 12 h drying the sample shows a basal spacing value of 1.62 nm. According to He et al [39], this should correspond to a transition structure between lateral-monolayer and lateral-bilayer for CTMA. In the rehydration process, OMt0.6 displays two reflections again at ∼2.70 nm and ∼1.90 nm, respectively.…”
Section: Basal Spacing Evolution Of Omtmentioning
confidence: 97%